Electronically Active Textiles - Dias, Tilak (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Electronically Active Textiles (e-textiles) are a type of textile material that has some form of electronic functionality. This can be achieved by attaching electronics onto the surface of the textile, incorporating electronic components as part of the fabrication of the textile itself, or by integrating electronics into the yarns or fibers that comprises the textile. The addition of electronic components can give textiles a wide range of new functions from lighting or heating to advanced sensing capabilities. As such, e-textiles have provided a platform for developing a range of new novel products in fields, such as healthcare, sports, protection, transport, and communications. The purpose of this volume is to report on the advances in the integration of electronics into textiles, and presents original research in the field of e-textiles as well as a comprehensive review of the evolution of e-Textiles. Topics include the fabrication and illumination of e-textiles and the use of e-textiles for temperature sensing.